Nitrite ion mitigates the formation of N-nitrosodimethylamine (NDMA) during chloramination of ranitidine - Seid, Mingizem Gashaw; Cho, Kangwoo; Lee, Changha; Park, Hyun-Mee; Hong, Seok Won (ELSEVIER, 2018)
Ranitidine (RNT) has been an important tertiary amine precursor of N-nitrosodimethylamine (NDMA) in chlorine-based water treatment, due to reaction with monochloramine (NH2Cl) with exceptionally high molar yields up to 90%. This study examined the effects of nitrite ions (NO2-) on the kinetics of NDMA formation during the chloramination of RNT under variable concentrations of dissolved oxygen (DO, 0.7-7.5 mg/L), RNT (5-30 mu M), NH2Cl (5-20 mM), NO2- or NO3- (0-2 mM) and pH (5.6-8.6). In the absence of the NO2-, the ultimate molar yield of NDMA after 6 h of reaction was primarily influenced by [DO] and pH, while marginally affected by initial [RNT] and [NH2Cl]. A kinetic model, prepared in accordance with the reaction sequence of NDMA formation, suggested that the rate determining step was accelerated with increasing [NH2Cl](0), [DO], and pH. A Kinetic study together with ultra-performance liquid chromatography-quadrupole-time of flight mass spectrometer (UPLC-Q-TOF MS) and gas chromatography (GC)/TOF MS analyses in parallel demonstrated that the nitrite ion inhibited the nucleophilic substitution of the terminal amine on NH2Cl, and reduced the pseudo-steady state concentration of N-peroxyl radicals, significantly decreasing the ultimate yields of NDMA. (c) 2018 Elsevier B.V. All rights reserved.